(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Chronic otitis media is a persistent inflammation of the middle ear mucosa lasting for more than three months. Identifying the clinical and paraclinical characteristics of chronic otitis media enables physicians to develop appropriate treatment strategies and minimize serious sequelae. The aim of this study was to describe the clinical and paraclinical characteristics of chronic otitis media in adults. Methods: A cross-sectional study was conducted on 70 patients aged 18 and older, diagnosed with chronic otitis media at Viet Tiep Friendship Hospital, Hai Phong in 2025. Results: Main subjective symptoms included: tinnitus (94.3%), hearing loss (90%), otorrhea (82.9%), ear pain (68.6%), and vertigo (40%). Otoscopy revealed that most patients had unilateral or bilateral tympanic membrane perforations. The majority of these perforations were central (73.2% in the right ear and 67.5% in the left ear), small to medium in size (>80%), and had smooth margins (95.1% in the right ear and 100% in the left ear). The middle ear mucosa was predominantly thickened and smooth (80.5% in the right ear and 90% in the left ear). Tympanosclerosis was absent in more than 80% of cases; consequently, the rate of required intervention for this condition was low (>90%). Conclusion: Clinical features observed in adults patients with chronic otitis media at Viet Tiep Friendship Hospital include tinnitus, hearing loss, ear discharge, ear pain, and dizziness. Most patients with chronic otitis media have tympanic membrane perforation, with the majority of perforations located centrally, ranging in size from small to medium, with clean edges, and thick, smooth tympanic mucosa. There is no tympanosclerosis, therefore the rate requiring intervention is low.